Ethnic Identity and Internal Difference of Fisher folk Community in the Coastal belt of South Kerala (International Journal of Food and Nutritional Sciences, 2022)
A fishing community is one in which most of its members have a fishing background. This article presents the ethnic fishermen group as a social group with different cultural practices. Social characteristics of people in society are determined by social relations. In this respect, the fishing community is understood as a part of the social world formed by the integration of social groups and relations. Churches such as churches, mosques and temples have had a great impact on the development of communities. Thus, representatives of religion know and behave in religion as well as in other areas of life according to the general configuration of the cultural context. In this context, racial discrimination in the fishing community can be brought to the fore. This article therefore focuses on many innovations by Shmuel Eisenstadt. This article attempts to analyze the ethnic groups of Muslim and Christian fishermen in the coastal area of Beema Palli. Beema Palli's field of work clearly illustrates religious diversity as an expression of the diverse beliefs that exist in different systems and locations. An important theoretical dimension of this approach is the social nature of leadership and diversity.